Association of sex with post-arrest care and outcomes after out-of-hospital cardiac arrest of initial shockable rhythm: a nationwide cohort study - Hosomi, Sanae; Irisawa, Taro; Nakao, Shunichiro; Zha, Ling; Kiyohara, Kousuke; Kitamura, Tetsuhisa; Ogura, Hiroshi; Oda, Jun (Frontiers in Cardiovascular Medicine, 2024)
Background: Research has described differences in the provision of prehospital treatment for women who experience out-of-hospital cardiac arrest. However, studies have reported conflicting results regarding survival outcomes or in-hospital interventions between sexes. Thus, this study aimed to investigate the association of sex with survival outcomes and in-hospital treatments in Japan. Methods: We retrospectively analyzed data from the Japanese Association for Acute Medicine-Outof-Hospital Cardiac Arrest Registry. Patients aged ≥18 years who presented with a shockable rhythm at the scene between June 2014 and December 2020 were included in our analysis. Outcome measures were 30-day survival and in-hospital interventions. We compared the outcomes between the sexes using multivariable logistic regression. Results: In total, 5,926 patients (4,270 men; 1,026 women) with out-of-hospital cardiac arrest were eligible for our analysis. The proportions of patients with 30-day survival outcomes were 39.5% (1685/4,270) and 37.4% (384/1,026) in the male and female groups, respectively (crude odds ratio, 0.92; 95% confidence interval, 0.80-1.06). Although there were no significant differences, survival outcomes tended to be better in women than in men in the multiple regression analysis (adjusted odds ratio, 1.38; 95% confidence interval, 0.82-2.33). Furthermore, there was no significant difference between the sexes in terms of patients who received extracorporeal cardiopulmonary resuscitation (adjusted odds ratio, 0.81; 95% confidence interval, 0.49-1.33) or targeted temperature management (adjusted odds ratio, 0.99; 95% confidence interval, 0.68-1.46). Conclusions: After adjusting for prognostic factors, there were no differences in survival rates and in-hospital interventions between men and women. 1 Introduction Out-of-hospital cardiac arrest (OHCA) is a major public health concern worldwide with high occurrence and mortality rates (1-3). In Japan, there are approximately 70,000 cases of OHCA annually (4,5). The incidence of emergency medical services (EMS)-treated OHCA in the United States is estimated to be 356,461, with nearly 90% of the cases being fatal (6). The overall prognosis and neurological outcomes are relatively poor following OHCA, and survival to hospital discharge after EMS-treated cardiac arrest is approximately 10% (1-6). The American Heart Association-